2020
DOI: 10.3389/fimmu.2020.00403
|View full text |Cite
|
Sign up to set email alerts
|

MuSK EAMG: Immunological Characterization and Suppression by Induction of Oral Tolerance

Abstract: Myasthenia gravis (MG) with antibodies to the muscle-specific receptor tyrosine kinase (MuSK) is a distinct subgroup of MG, affecting 5-8% of all MG patients. MuSK, a receptor tyrosine kinase, is expressed at the neuromuscular junctions (NMJs) from the earliest stages of synaptogenesis and plays a crucial role in the development and maintenance of the NMJ. MuSK-MG patients are more severely affected and more refractory to treatments currently used for MG. Most patients require long-term immunosuppression, stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Another approach that gains ground as an antigen-specific therapy is the induction of tolerance towards the autoantigens, by administration of disease-relevant antigen derived domains and peptides. A recent study using MuSK-induced EAMG in mice demonstrated the potential for tolerance induction by oral administration of recombinant MuSK domains ( 248 ). However, MuSK administration took place prior to induction, so further studies are necessary to evaluate the actual therapeutic potential.…”
Section: Treatments Of Igg4 Neurological Diseasesmentioning
confidence: 99%
“…Another approach that gains ground as an antigen-specific therapy is the induction of tolerance towards the autoantigens, by administration of disease-relevant antigen derived domains and peptides. A recent study using MuSK-induced EAMG in mice demonstrated the potential for tolerance induction by oral administration of recombinant MuSK domains ( 248 ). However, MuSK administration took place prior to induction, so further studies are necessary to evaluate the actual therapeutic potential.…”
Section: Treatments Of Igg4 Neurological Diseasesmentioning
confidence: 99%
“…In this case treatment would not have an immediate impact, but it would aim at a long-lasting or permanent effect. Indeed, studies have shown that EAMG symptoms can be prevented or ameliorated by oral or nasal administration of AChR or MuSK domains (140)(141)(142)(143)(144). In most studies the extracellular domain of the AChR α subunit has been used, while the response was not affected by the use of syngeneic (rat) or xenogeneic (human) AChR sequences (145).…”
Section: Development Of Therapies Based On Autoantigen Specificitymentioning
confidence: 99%
“…Conjugation of antigen derived peptides to immunomodulating protein domains as a means of targeting has also been explored to improve treatment potency with promising results (150). In most cases of tolerance induction, a shift in the T cell responses from Th1 to Th2 and/or Th3 was involved in mediating the therapeutic effect, evidenced by changes in the respective cytokine levels, mostly reduction in IFN-g, IL-2 and IL-12 and increase in IL-10 and TGF-β expression, accompanied by changes in the AChR IgG subclass distribution (144,(151)(152)(153).…”
Section: Development Of Therapies Based On Autoantigen Specificitymentioning
confidence: 99%
“…The same group (96) also reported that tacrolimus, an immunosuppressant for AChR+ MG, inhibited Th1 and Th17 responses, and reduced Treg frequencies of in vitro cultured peripheral blood mononuclear cells (PBMCs) from MuSK+ MG patients. Reuveni et al (97) reported that a mouse model of MuSK+ EAMG had decreased Treg frequencies and FoxP3 expression, the latter of which was restored by oral administration of recombinant MuSK protein.…”
Section: Regulatory T Cellsmentioning
confidence: 99%